An interdisciplinary analysis of behavioral genetics : bridging philosophy and science - Cotanda, Vicente Dall'igna (2024)
This thesis examines the historical but ongoing nature vs. nurture debate, tracing its roots from ancient Greek philosophy through the latest advancements in behavioral genetics. From a philosophical perspective, it examines the interplay between genetics and environment in shaping human behavior, analyzing the conceptual foundations, methodologies, and findings of behavioral genetics. This work also considers how research in behavior genetics, which aims to explore the constitutive forces of nature and nurture, is constructed interdisciplinarily, highlighting the epistemological challenges of understanding the development of human psychological differences. By integrating insights from various disciplines, this work aims to connect science with philosophy to enhance the conceptual clarity of behavioral genetics and demonstrate its relevance to broader philosophical and scientific discussions